Effects of compost tea on the spatial distribution of soil nutrients and growth of cotton under different fertilization strategies. (15th June 2022) - Luo, Tong; Ma, Lin; Wei, Changzhou; Li, Junhua
Abstract: Compost tea comes from a wide range of sources and can provide nutrients for crops and improve soil quality. In order to explore the effects of fertilization frequencies of compost tea on the spatial distribution of nutrients and the uptake by cotton, a trial comprised no fertilization treatment (CK) and three fertilizer treatments, that is, the application of a fixed amount of fertilizer at four (F3), two (F5), or one (F9) irrigation cycle, and each irrigation cycle was 10 days. The total amount of nutrients (N, P2 O5, K2 O) in fertilization treatment were all 18 g, and their amount of fertilization each time was 1/3, 1/5 and 1/9 of the total fertilizer, respectively. The results showed that in 0–10 cm soil layers, high-frequency fertilization (F9) reduced the soil pH by 5.6% compared with F3, the soil nutrient content of F3 treatment at seedling stage was significantly higher than that of the other two treatments by 71.9%–272.3%, however, the 20–40 cm soil layer was hardly affected by fertilization; The nutrient accumulation of cotton in F3 treatment was 17.1%–32.4% higher than that in the other two treatments, and the highest dry matter and recovery efficiency were also obtained under the F3 treatment. In conclusion, increasing the proportion of fertilization in seedling stage (F3) can increase the uptake and utilization of nutrients by cotton; While high-frequency fertilization (F9) can reduce the pH of calcareous soil. This study provides a basis for fertilizer optimization and soil quality improvement of composted tea.